PEMAHAMAN APARATUR PEMERINTAH TERHADAP PENERAPAN AKUNTANSI KEUANGAN DEMI TERCIPTANYA GOOD GOVERNANCE - Herlin, -; Effendi, Yanto (JURNAL EKOMBIS REVIEW, 2017)
Herlin dan Yanto Effendi: The purpose of this study to determine the understanding of government apparatus in the area of financial accounting application in order to realize good governance. Government Personnel Rejang Lebong still has a bit of an apparatus / HR background in accounting, from 25 respondents, only 9 respondents (36%) accounting background and the rest comes from other disciplines.The results showed that the correlation obtained the r value of 0, 203 a positive correlation between the variables x and y variables where the value of r lies in the interval 0 <r <1, and has a level of low relation because r value lies in the interval coefficient of 0, 20 -, 399. Reliability test alpha value of 0.60 is said to be reliable so that the new variable of educational background alpha coefficient of 0.6123, the education and training of alpha coefficient of 0.622 and Awareness Regional Financial Accounting alpha coefficient of 0.710. T-count value <the t-table, t-count equal to 3,699 while the t-table at significant level of 0.05% t-table of 4,946, this means that the level of understanding of government officials in Rejang Lebong specifically the application of financial accounting still weak or low , so they need to increase human resources through education, training, and understanding of financial accounting has become a standard government.Key words: Good Governance.